(3fRgI GdCHUGQ Ydi efXheI GdEeGe GdYWGQs - (3MSf Hf Ydj bhjOQ GdNdjdj GdTGaYjs; (3MSf GdYWGQs ((3EHQGgje Hf eMeO GdabjQ s)
(3ChdgG (B:s
(3hHYO, aCbhd hCfG GdabjQ MSf Hf Ydj bhjOQ, GdefShH Edi eOjfI GdNdjd s
(3BNQgG (B:s
(3ZjQJ NWHJg hROJ ajg GdNhGJe MJi bGd bGFdge(B: (3Ef gPG GdTQM CYLhHI agPG ChbJ JeGeg s
(3bhHdJ Ydi YOI fSN UMjMIs
(3HgG fXGe GdJYbjHIs
(3HBNQgG JQLeI GdeDda dTjNg MSf GdYWGQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs